How Do Laparoscopic And Open Surgical Techniques Compare In Terms Of Patient Outcomes For Acute Appendicitis? - Ikhwan Edo Rambe; Ivani Junianti (The Indonesian Journal of General Medicine, 2025)
Introduction: Appendectomy is a common surgical procedure performed to treat acute appendicitis. This study aims to compare the clinical outcomes of laparoscopic appendectomy (LA) versus open appendectomy (OA) based on multiple studies. Methods: A comprehensive review of 40 high-quality studies, including randomized controlled trials and observational studies, was conducted. Primary outcomes analyzed were postoperative pain, hospital length of stay, complication rates, wound infection rates, and return to work time. Data on operative time and surgical techniques were also extracted. Results: The analysis showed that LA generally resulted in lower postoperative pain scores compared to OA. Hospital stay was significantly shorter in LA patients, with many studies reporting stays of 1-2 days versus 3-4 days for OA. Complication and wound infection rates were consistently lower in the LA group. Operative time varied, with some studies showing longer durations for LA, while others reported comparable times. Return to work and normal activities occurred earlier in LA patients. Discussion: The minimally invasive nature of LA contributes to reduced pain, faster recovery, and fewer infections. Although operative time may be longer in some cases, the overall benefits favor LA. Variations in study design and patient demographics were noted but did not significantly affect the overall trend. Conclusion: Laparoscopic appendectomy offers superior clinical outcomes compared to open appendectomy, including reduced pain, shorter hospital stay, and lower complication rates. It should be considered the preferred surgical approach for acute appendicitis when feasible.